SAkuraBONSAI: Protocol design of a novel, prospective study to explore clinical, imaging, and biomarker outcomes in patients with AQP4-IgG-seropositive neuromyelitis optica spectrum disorder receiving open-label satralizumab - Bennett, Jeffrey L.; Fujihara, Kazuo; Kim, Ho Jin; Marignier, Romain; O'Connor, Kevin C.; Sergott, Robert C.; Traboulsee, Anthony; Wiendl, Heinz; Wuerfel, Jens; Zamvil, Scott S.; Anania, Veronica G.; Buffels, Regine; et al. (Frontiers in Neurology, 2023)
Background: Neuromyelitis optica spectrum disorder (NMOSD) is a rare, autoimmune disease of the central nervous system that produces acute, unpredictable relapses causing cumulative neurological disability. Satralizumab, a humanized, monoclonal recycling antibody that targets the interleukin-6 receptor, reduced NMOSD relapse risk vs placebo in two Phase 3 trials: SAkuraSky (satralizumab ± immunosuppressive therapy; NCT02028884); SAkuraStar (satralizumab monotherapy; NCT02073279). Satralizumab is approved to treat aquaporin-4 IgG-seropositive (AQP4-IgG+) NMOSD. SAkuraBONSAI (NCT05269667) will explore fluid and imaging biomarkers to better understand the mechanism of action of satralizumab and the neuronal and immunological changes following treatment in AQP4-IgG+ NMOSD. Objectives: SAkuraBONSAI will evaluate clinical disease activity measures, patient-reported outcomes (PROs), pharmacokinetics, and safety of satralizumab in AQP4-IgG+ NMOSD. Correlations between imaging markers (magnetic resonance imaging [MRI] and optical coherence tomography [OCT]) and blood and cerebrospinal fluid (CSF) biomarkers will be investigated. Study design: SAkuraBONSAI is a prospective, open-label, multicenter, international, Phase 4 study that will enroll approximately 100 adults (18-74 years) with AQP4-IgG+ NMOSD. This study includes two patient cohorts: newly diagnosed, treatment-naïve patients (Cohort 1; n=60); and inadequate responders to recent (<6 months) rituximab infusion (Cohort 2; n=40). Satralizumab monotherapy (120mg) will be administered subcutaneously at Weeks 0, 2, 4, and Q4W thereafter for a total of 92 weeks. Endpoints: Disease activity related to relapses (proportion relapse-free, annualized relapse rate, time to relapse, and relapse severity), disability progression (Expanded Disability Status Scale), cognition (Symbol Digit Modalities Test), and ophthalmological changes (visual acuity; National Eye Institute Visual Function Questionnaire-25) will all be assessed. Peri-papillary retinal nerve fiber layer and ganglion cell complex thickness will be monitored using advanced OCT (retinal nerve fiber layer and ganglion cell plus inner plexiform layer thickness). Lesion activity and atrophy will be monitored by MRI. Pharmacokinetics, PROs, and blood and CSF mechanistic biomarkers will be assessed regularly. Safety outcomes include the incidence and severity of adverse events. Conclusions: SAkuraBONSAI will incorporate comprehensive imaging, fluid biomarker, and clinical assessments in patients with AQP4-IgG+ NMOSD. SAkuraBONSAI will provide new insights into the mechanism of action of satralizumab in NMOSD, while offering the opportunity to identify clinically relevant neurological, immunological, and imaging markers.